2000
DOI: 10.1093/bja/85.3.364
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous opioids reduce airway irritation during induction of anaesthesia with desflurane in adults†

Abstract: Desflurane is not used for the induction of anaesthesia despite its favourable pharmacokinetic characteristics because it causes airway irritation. We investigated whether pretreatment with i.v. narcotics reduced unwanted effects. One hundred and eighty adults were randomized to three groups (60 per group) to receive i.v. saline, fentanyl 1 microgram kg-1 and morphine 0.1 mg kg-1, respectively, before inhalational induction with desflurane in nitrous oxide and oxygen. Mean time to loss of response to commands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
44
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 16 publications
0
44
0
Order By: Relevance
“…Indeed, inhalation of desflurane [greater than 1 minimum alveolar concentration (MAC)] and isoflurane (greater than 1.5 MAC) produces airway irritation in humans, and therefore, these GAs are avoided as induction agents (Eger, 1995;Kong et al, 2000). We have shown recently that these pungent GAs excite sensory neurons by directly activating the transient receptor potential (TRP) channel TRPA1 (mustard-oil receptor) (Matta et al, 2008).…”
mentioning
confidence: 99%
“…Indeed, inhalation of desflurane [greater than 1 minimum alveolar concentration (MAC)] and isoflurane (greater than 1.5 MAC) produces airway irritation in humans, and therefore, these GAs are avoided as induction agents (Eger, 1995;Kong et al, 2000). We have shown recently that these pungent GAs excite sensory neurons by directly activating the transient receptor potential (TRP) channel TRPA1 (mustard-oil receptor) (Matta et al, 2008).…”
mentioning
confidence: 99%
“…The reason of stable vital signs was fentanyl. Kong and colleague [7] suggested that intravenous opioids reduce airway In conclusion, we found that early inhalation of desflurane (6%) to the patient pretreated with fentanyl attenuates adverse hemodynamic responses to nasotracheal intubation without airway irritation but has no effect on rocuronium-induced pain. …”
mentioning
confidence: 53%
“…Therefore they have a general tendency to start desflurane inhalation after tracheal intubation. But several studies [6][7][8][9] have demonstrated that desflurane can be used in inhalation induction. We hypothesized that early inhalation of desflurane would be good for cardiovascular stability during intubation and also rocuronium injection pain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(5) Although these side effects can be somewhat reduced by pre-treatment with morphine. (6) this is rather impractical and desflurane is rarely used for induction of anaesthesia. In contrast, sevoflurane has a less pungent, fruitier smell and permits a much smoother induction of anaesthesia with a remarkable absence of airway irritability.…”
Section: Introductionmentioning
confidence: 99%